The Influence of Work Discipline and Self-Efficacy on Employee Performance at the Department of Agriculture and Food Security, Maros Regency - Riswahyudi; Jusri; Sundari Rahman (Journal of Economics and Management Technologies, 2025)
The Objectives – This study aims to determine the influence of work discipline and self-efficacy on the performance of employees in Maros Regency. The main objective of this study is to determine whether work discipline and self-efficacy have a significant influence on the dominant factors that influence the performance of employees in the Maros Regency service. The Methods/approaches -This study uses quantitative methods and data collection using questionnaires. In this study, two independent variables are used, namely (X1) Work discipline and (X2) Self-efficacy and one dependent variable, namely (Y) Employee performance. The sample required in this study is 101 respondents, and the data analysis techniques used are descriptive statistical tests, validity tests, reliability tests, multiple linear regression, t-tests, f-tests, and coefficients of determination R2. This test was carried out using SPSS software vol 25. The Results – The results of the t-test study indicate that the work discipline variable has no positive and insignificant effect on employee performance, while the self-efficacy variable has a positive and significant effect on employee performance. Based on the results of the f-test, the work discipline and self-efficacy variables have a simultaneous effect on employee performance. The Research Implications – This research contributes to the understanding of employee behavior in the service so that discipline is maintained and the self-efficacy given to the service continues to run smoothly